2010
DOI: 10.1007/s10528-010-9358-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genetic Differentiation in Geographic Populations of Labeo calbasu Using Allozyme Markers

Abstract: The population structure of Labeo calbasu from 11 rivers belonging to the Indus, Ganges, Bhima, Mahanadi, and Godavari basins was investigated using allozyme marker systems. Seven out of 20 allozyme loci (35%) were polymorphic (P < 0.99). Both probability and score tests indicated significant deviation of genotype proportions from Hardy-Weinberg expectations at two loci, XDH* (Mahanadi, Bhima, and Godavari) and G6PDH* (Mahanadi). A pairwise genetic homogeneity test and F (ST) values indicated a low-to-moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Allozymes (Markert and Moller 1959), random amplified polymorphic DNA (Williams et al 1990;Welsh and McClelland 1990), and microsatellites (Tautz 1989) are the common genetic markers used for population genetics and pedigree analysis and for taxonomic discrimination of species (Klinbunga et al 2000;Piel and Nutt 2000;Callejas and Ochando 2002;Ma and Chen 2011;Sen et al 2010;Singh et al 2010;Chaturvedi et al 2011). Several authors have reported comparative assessments of these three markers in fishes (Cagigas et al 1999;Sun et al 1999;Mandal et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Allozymes (Markert and Moller 1959), random amplified polymorphic DNA (Williams et al 1990;Welsh and McClelland 1990), and microsatellites (Tautz 1989) are the common genetic markers used for population genetics and pedigree analysis and for taxonomic discrimination of species (Klinbunga et al 2000;Piel and Nutt 2000;Callejas and Ochando 2002;Ma and Chen 2011;Sen et al 2010;Singh et al 2010;Chaturvedi et al 2011). Several authors have reported comparative assessments of these three markers in fishes (Cagigas et al 1999;Sun et al 1999;Mandal et al 2009).…”
Section: Discussionmentioning
confidence: 99%